FORMALIZAÇÃO DA TRANSFORMAÇÃO DE MODELOS UTILIZANDO A LINGUAGEM Z - MENDES, Carlos César Gomes (2011)
In this thesis, an approach based on Set Theory and on the Z Formal Language Specification is presented to formalize the transformations between models in the context of Model Driven Engineering (MDE). The motivation for this research is justified due the ambiguities and inconsistencies present in the models of transformation used to abstract the model transformation process in the MDE context. The precision absence in these the models lead the user to misinterpret complex structures present in the mapping of the source model elements to the target model elements. In this context, we proposed to develop a formal methodology that eliminates the ambiguities and inconsistencies present in the informal representations of model transformation in MDE. To solve this problem, a Formal and Conceptual Framework is developed that groups the elements involved in the process of transformation, represented by mathematical artifacts from the Set Theory and specified on Z language. This Framework is validated through a case study that contains complex transformations, tested on the mathematical proof tool Z/EVES, which supports statements made in Z language.